2005
DOI: 10.1211/jpp.57.11.0017
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Polygala paniculata extract against methylmercury-induced neurotoxicity in mice

Abstract: We have examined the possible protective effects of Polygala paniculata extract against methylmercury (MeHg)-induced neurotoxicity in adult mice. MeHg was diluted in drinking water (40 mg L(-1), freely available) and the hydroalcoholic Polygala extract was diluted in a 150 mM NaCl solution and administered by gavage (100 mg kg(-1) b.w., twice a day). After a two-week treatment, MeHg exposure significantly inhibited glutathione peroxidase and increased glutathione reductase activity, while the levels of thiobar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 29 publications
4
56
0
Order By: Relevance
“…Some reports indicate that dietary fat can influence oxidative DNA damage, nephrotoxicity, and steroidogenic enzyme activities after MeHg exposure (Grotto et al, 2011;Jin et al, 2008Jin et al, , 2009McVey et al, 2008). However, the human diet varies widely, and some reports have shown that foodstuffs other than seafood may also prevent MeHg toxicity and accumulation (Abdalla et al, 2010;Farina et al, 2005;Lee et al, 1999;Rowland et al, 1986;Sumathi et al, 2012). Therefore, daily fish consumption may alleviate relatively few health risks.…”
mentioning
confidence: 99%
“…Some reports indicate that dietary fat can influence oxidative DNA damage, nephrotoxicity, and steroidogenic enzyme activities after MeHg exposure (Grotto et al, 2011;Jin et al, 2008Jin et al, , 2009McVey et al, 2008). However, the human diet varies widely, and some reports have shown that foodstuffs other than seafood may also prevent MeHg toxicity and accumulation (Abdalla et al, 2010;Farina et al, 2005;Lee et al, 1999;Rowland et al, 1986;Sumathi et al, 2012). Therefore, daily fish consumption may alleviate relatively few health risks.…”
mentioning
confidence: 99%
“…Scientific studies in isolated cells and in animals have confirmed the biological activities of the plants from genus Polygala [2-10]. The chemical constituents of Polygala , coumarins, steroids, saponins, lignans, flavonoids and xanthones confer to these plants valuable pharmacological properties [7][8][9][10][11][12][13].Recently, we have demonstrated that Polygala sabulosa hydroalcoholic extract (HE) A. W. Bennett (Polygalaceae) produced antinociceptive action against the acetic acidinduced visceral nociception. The presence of styryl-2-pyrones, coumarin (scopoletin) and steroid ( α -spinasterol) gives to the plant a potent antinociceptive effect [9].…”
mentioning
confidence: 99%
“…Scientific studies in isolated cells and in animals have confirmed the biological activities of the plants from genus Polygala [2-10]. The chemical constituents of Polygala , coumarins, steroids, saponins, lignans, flavonoids and xanthones confer to these plants valuable pharmacological properties [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Clinical symptoms o f Hg toxicity include cerebellar ataxia, constriction o f the visual field and damage to the auditory region o f the temporal lobe (Clarkson, 1997;Ekino et al, 2007). Clinical symptoms o f Hg intoxication include the loss o f motor coordination (Bellum et al, 2012), abnormal movements and convulsions (Takeuchi et al, 1977) and loss o f balance (Farina et al, 2005). Macaque monkeys had impaired high-frequency hearing and visual damage following postnatal MeHg exposure (Newland and Paletz, 2000).…”
Section: A Backgroundmentioning
confidence: 99%
“…We would expect clinical symptoms of Hg intoxication to include the loss o f motor coordination (Bellum et al, 2012), abnormal movements and convulsions (Takeuchi et al, 1977), loss of balance (Farina et al, 2005), and reduced passive avoidance. The harvesters did not observe any abnormal movements or behaviour in the beluga whales prior to harpooning, which suggests that Hg exposure in the eleven whales analyzed in this study were not exhibiting clinical symptoms of Hg intoxication.…”
Section: Integration Of Multiple Lines Of Evidencementioning
confidence: 99%